To segregate or to integrate: education politics and democracy - David de la Croix; Matthias Doepke (Institute for the Study of Labor (IZA), 2007)
The governments of nearly all countries are major providers of primary and secondary education to their citizens. In some countries, however, public schools coexist with private schools, while in others the government is the sole provider of education. In this study, we ask why different societies make different choices regarding the mix of private and public schooling. We develop a theory which integrates private education and fertility decisions with voting on public schooling expenditures. In a given political environment, high income inequality leads to more private education, as rich people opt out of the public system. More private education, in turn, results in an improved quality of public education, because public spending can be concentrated on fewer students. Comparing across political systems, we find that concentration of political power can lead to multiple equilibria in the determination of public education spending. The main predictions of the theory are consistent with state-level and micro data from the United States as well as cross-country evidence from the PISA study.
Keywords: 330; Bildungswesen; Schule; Privatschule; Bildungsertrag; Politisches System; Theorie; OECD-Staaten